PENELITIAN AGAMA: PEDEKATAN FENOMENOLOGI RUDOLF OTTO - Mufid, Mufid (Jurnal Bestari, 1993)
There are many "mystries" in every revealed religion. The essence of God, for Instance, is a kind of absolute and ultimate concept in religious discourse. His omnipresence, however, can be traced to many kinds of human and mondial experience, In other words, the existence of God connot be ignored by His creatures. Everyman who conceives His presence to this world will be able to be closer to Him. Consequently, he can do everything in line with His teachings, just for the sake of His blessing and mercy. To get this ideal goal, the method which offered by Rudolf Otto can be adopted to every religion. It is, of course, depending and based on each religion which is beleived by man. Moslem, for example, can adopt it to be closer to Allah, The Grace an The Merciful.